PENGARUH PEMBIASAAN KERJASAMA DALAM MENINGKATKAN KARAKTER GOTONG ROYONG DAN TANGGUNG JAWAB DI KELAS V SEKOLAH DASAR - Muhammad Athif Razani Widayat; Asrial; Alirmansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the importance of building Mutual Cooperation (Gotong Royong) and Responsibility characters at the elementary school level to balance academic achievement and students' affective development. At SDN 80/1 Muara Bulian, a phenomenon was observed where students remained passive in groups and showed a lack of responsibility toward collective tasks. This study aims to explain and analyze the influence of cooperation habituation in enhancing mutual cooperation and responsibility characters among fifth-grade elementary school students. The research method used is a quantitative approach with a quasi-experimental design. The population of this study consisted of all fifth-grade students at SDN 80/1 Muara Bulian, with class V A as the experimental group receiving the cooperation habituation treatment and class V B as the control group. Data collection techniques were conducted through structured observations using character assessment rubrics validated by experts. Data analysis involved prerequisite tests (normality and heteroscedasticity) and hypothesis testing through simple linear regression assisted by the SPSS program. The results showed a positive and significant influence of cooperation habituation on students' character. Statistically, the cooperation habituation variable contributed 14.7% to the improvement of mutual cooperation character and 11.7% to responsibility character. This is evidenced by a positive regression coefficient value, indicating that every increase in the intensity of cooperation habituation significantly improves student character scores. The conclusion of this research is that the habituation method is an effective pedagogical strategy for internalizing social values within the elementary school ecosystem.